Clinical genetics of spondylocostal dysostosis: A mini review - Umair, Muhammad; Younus, Muhammad; Shafiq, Sarfraz; Nayab, Anam; Alfadhel, Majid (Frontiers in Genetics, 2022)
Spondylocostal dysostosis is a genetic defect identified by severe ribs and vertebrae malformations. In recent years, extensive clinical and molecular diagnosis advancements enabled us to identify disease-causing genes for such severe conditions. Identification of novel genes enabled us to understand the developmental biology and molecular and cellular mechanisms involved in the etiology of these rare diseases. Here, we discuss the clinical and molecular targets associated with Spondylocostal dysostosis, including clinical evaluation, genes, and pathways. This review might help us understand the basics of this severe disorder for more proper clinical characterization and might help in therapeutic strategies.